CHILD PROTECTION INSTITUTIONS AS AN IMPLEMENTATION OF THE VALUE OF RAHMATAN LIL 'ALAMIN IN ISLAMIC FAITH - Astri Amanda Putri; Maulida Rahmi Lubis; Mardhiah Abbas (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The value of Rahmatan lil 'alamin in Islamic creed emphasizes compassion, justice, and protection for all beings, including children as a vulnerable group. This study aims to analyze the role of child protection institutions as an implementation of the value of Rahmatan lil 'alamin from the perspective of Islamic aqidah. The research uses a qualitative approach through library research by examining relevant literature on Islamic creed and child protection. The findings indicate that child protection institutions play an important role in realizing the value of compassion through efforts to prevent violence, fulfill children's rights, and provide legal and social protection. This implementation shows that child protection is not only a social and legal obligation but also has a theological foundation in Islam as a manifestation of mercy for all creation.